Complex SNP-Based Haplotypes in Three Human Helicases: Implications for Cancer Association Studies - Trikka, Dimitra; Fang, Zhe; Renwick, Alex; Jones, Sally H.; Chakraborty, Ranajit; Kimmel, Marek; Nelson, David L. (Genome Research, 2002)
We have initiated a candidate gene approach to study variation and predisposition to cancer in the four major ethnic groups that constitute the U.S. population (African Americans, Caucasians, Hispanics, and Asians). We resequenced portions of three helicase genes (BLM, WRN, and RECQL) identifying a total of 37 noncoding single nucleotide polymorphisms (SNPs). Haplotype inference predicted 50 haplotypes in BLM, 56 in WRN, and 47 in RECQL in a sample of 600 chromosomes. Approximately 10% of the predicted haplotypes were shared among all ethnic groups. Linkage disequilibrium and recombination effects showed that each locus has taken a diverse evolutionary path. Primate DNA analysis of the same loci revealed one human haplotype per gene shared with the great apes, indicating that the observed diversity occurred since the divergence of humans from the last common ancestor. In BLM, we confirmed the presence of a founder haplotype among Ashkenazi Jews homozygous for theblm Ash mutation. The cosegregating haplotype was seen in all (6/6) samples of Ashkenazi descent, whereas in the general population it has a low frequency (0.02) and was not found in African Americans. In WRN, ethnic samples were studied for their haplotype content and the presence or absence of six previously described coding SNPs (cSNPs). Hispanic individuals carrying two of these cSNPs showed a 60% increase in the frequency of a common haplotype (haplotype No. 28). In the pooled sample, no association was found. Because (1) the majority of the haplotypes are population specific and (2) the patterns of linkage disequilibrium, recombination, and haplotype diversity are markedly different between gene regions, these data show the importance of either ethnically matched controls or within-family-based disease-gene association studies.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. AC006559. Online supplemental material available at http://www.genome.org]